Age and early life adversity shape heterogeneity of the epigenome across tissues in macaques - Baptiste Sadoughi; Rachel M. Petersen; Sam K. Patterson; Elizabeth Slikas; Christine Adjangba; Nicholas Ryan; Christina E. Costa; Laura E. Newman; Marina M. Watowich; Cameron R. Kelsey; Ashlee Greenier; Elisabeth A. Goldman; et al. (Science, 2026)
Age and early life adversity (ELA) are key determinants of health, but whether they affect similar physiological mechanisms across tissues is unknown. We generated DNA methylation (DNAm) profiles across 14 tissues in 237 semi–free-ranging rhesus macaques with naturally occurring ELA. Age-associated DNAm was predominantly tissue dependent, yet tissue-specific epigenetic clocks showed that epigenetic aging was relatively consistent within individuals. ELA effects were adversity dependent, but each ELA exerted coordinated effects across tissues. Although ELA targeted many of the same loci as age, the directions of effects differed, which indicates that ELA does not uniformly increase epigenetic age. Instead, ELA leaves a coordinated, cross-tissue epigenetic signature that is distinct from—yet intertwined with—age-related differences, which advances our understanding of how early environments sculpt the molecular foundations of aging and disease.